Peroxide-free redox initiating systems for polymerization in mild conditions. Issue 12 (4th March 2021) - Arar, Ahmad; Mousawi, Assi Al; Morlet-Savary, Fabrice; Lalevée, Jacques
Abstract : Redox free radical polymerization (RFRP) is considered as a cost-effective technique for the production of polymers in a very short time scale and without any energy consumption. Abstract : Redox free radical polymerization (RFRP) is considered as a cost-effective technique for the production of polymers in a very short time scale and without any energy consumption. Its principle is based on blending two components (2K for two cartridges) composed of an oxidizing and a reducing agent, respectively. In this paper, original Redox Initiating Systems (RISs) comprising metal salts as oxidizing agents and reducing agents are developed for mild conditions (at room temperature, under air and without monomer purification or stabilizer removal). An economic, low toxicity and high stability process is attained. A good control of the gel time is also possible. Based on electron spin resonance experiments, an original chemical mechanism is also provided for these redox initiators.